Combined and additive effects of assembly tasks and constrained body postures - Skelton, Sarah Anne (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2007)
Despite extensive research into musculoskeletal disorders (MSDs) they continue to plague workers. Manual materials handling (MMH), in particular the concurrence of load manipulation and awkward body posture, has been identified as a key factor in the onset of MSDs. Only a few studies have looked at the interaction between manipulation tasks and working posture during assembly tasks and as a result their relationship has not been widely explored. Assessing the stresses resulting from individual task factors and body posture in isolation and adding them together may be too simplified to estimate an overall risk profile, since this does not take into account that there may be a non-linear interaction in strain responses when manipulation task and body posture interact. Therefore, the present study investigated biophysical, physiological and psychophysical responses to combined tasks, rather than individual tasks of body posture and manipulative tasks. The objective of the research was to establish the interactive effects of constrained body postures and manipulative tasks and to identify whether a cumulative or compensatory reaction occurs during this interaction. Nine conditions were assessed in a laboratory setting, which included combinations of three working postures (standing, sitting and stooping) and three assembly tasks (torque wrenching, precision and no task). Thirty-six subjects were required to complete all nine conditions, with each condition lasting ninety seconds. Muscle activity was recorded for seven muscles from the upper extremity, trunk and lower extremity regions and was complemented by physiological (heart rate, tidal volume, minute ventilation, oxygen consumption, energy expenditure and breathing frequency) and psychophysical (body discomfort) data. At the completion of all nine conditions subjects completed a retrospective psychophysical rating questionnaire pertaining to discomfort felt during the conditions. Responses obtained for the different task and posture combinations revealed compensatory reactions (additive > combined) for most of the conditions assessed for the biomechanical and physiological responses. In the majority of cases for muscle activity, no significant differences were found between the combined and the additive effects (p < 0.05), while for the physiological responses there were mostly significant differences observed. Psychophysical responses indicated that there was a significant difference overall between the additive and combined effects. The results of this study demonstrate that in order to identify risk areas, manipulation tasks and constrained working postures may be considered either in isolation and added together (additive) or as a combined task, since there were very few significant differences observed between these two effects. Further studies are required, however, to provide conclusive evidence.
Keywords: Musculoskeletal system -- Diseases; Human engineering; Posture; Posture disorders; Work -- Physiological aspects; Occupational diseases; Manual work; Job stress